2017
DOI: 10.1016/j.applthermaleng.2016.08.151
|View full text |Cite
|
Sign up to set email alerts
|

Prevent thermal runaway of lithium-ion batteries with minichannel cooling

Abstract: Thermal management on lithium-ion batteries is a crucial problem for the performance, lifetime, and safety of electric vehicles (EVs) and hybrid electric vehicles (HEVs). Fire and explosion can be triggered by thermal runaway if the temperature of the lithium-ion batteries is not maintained properly. In this work, a minichannel cooling system was designed at the battery module level, and its efficacy on thermal runaway mitigation was investigated. Nail penetration was employed to simulate the internal short ci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
50
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 234 publications
(50 citation statements)
references
References 36 publications
0
50
0
Order By: Relevance
“…In the actual energy storage system of an EV, the capacity of each battery cell is about three orders of magnitude larger and may easily reach 170 °C in less than a minute . If the peak temperature increase in these higher‐capacity cells can be reduced by ∼40%, the risk of thermal runaway may be significantly lowered . Note that the relationship between cell size and Δ T peak is nonlinear and is also dependent on other factors such as battery chemistry, state of charge, geometry, and ambient temperature .…”
Section: Resultsmentioning
confidence: 99%
“…In the actual energy storage system of an EV, the capacity of each battery cell is about three orders of magnitude larger and may easily reach 170 °C in less than a minute . If the peak temperature increase in these higher‐capacity cells can be reduced by ∼40%, the risk of thermal runaway may be significantly lowered . Note that the relationship between cell size and Δ T peak is nonlinear and is also dependent on other factors such as battery chemistry, state of charge, geometry, and ambient temperature .…”
Section: Resultsmentioning
confidence: 99%
“…Thermal runaway occurs when the temperature of the lithium ion batteries rises above the allowable operating conditions, which occurs when the cooling system is unable to effectively remove the generated heat . Xu et al proposed a mini channel liquid‐based cooling system that is designed on a battery modular level, and the system performance was analyzed for severe conditions of internal short circuit. Internal short circuit in batteries can result from manufacturing defects or/and vehicle collisions.…”
Section: Battery Thermal Management Systems (Btmss)mentioning
confidence: 99%
“…Internal short circuit in batteries can result from manufacturing defects or/and vehicle collisions. Xu et al simulated a battery internal short circuit by employing nail penetration. Xu et al concluded that their proposed system of mini channel cooling system was not able to stop thermal runaway, but it was able to prevent the propagation of thermal runaway between the cells.…”
Section: Battery Thermal Management Systems (Btmss)mentioning
confidence: 99%
“…19 A battery thermal management system (BTMS) is needed since extreme temperature can significantly affect safety and durability of EVs. For mitigating these potential hazards, Xu et al 22 and Lan et al 23 developed a novel BTMS based on aluminum mini-channel tubes and applied it to a single prismatic Li-ion battery under different discharge rates. For mitigating these potential hazards, Xu et al 22 and Lan et al 23 developed a novel BTMS based on aluminum mini-channel tubes and applied it to a single prismatic Li-ion battery under different discharge rates.…”
Section: Literature Reviewmentioning
confidence: 99%
“…20,21 More severely, fatal fires or explosions could be triggered by thermal runaway if the battery thermal condition can not be appropriately managed. For mitigating these potential hazards, Xu et al 22 and Lan et al 23 developed a novel BTMS based on aluminum mini-channel tubes and applied it to a single prismatic Li-ion battery under different discharge rates. The uniform temperature distribution inside the battery cell indicates that the mini-channel cooling system can prevent thermal runaway from propagation between cells.…”
Section: Literature Reviewmentioning
confidence: 99%